(untitled) (Bangladesh Journal of Medical Education, 2023)
Background: The understanding of the medical career decision-making process is important to aid career counseling and thus prevent wrong choices, support medical graduates in their choice and promote faster choices. An understanding of the factors which influence doctors’ career choices, and how attitudes vary among doctors who choose different specialties, is important for all those involved in the teaching and training of doctors. Objectives: This study was done to explore views of final phase undergraduate medical students of Bangladesh about the personal & familial factors those influence their future career selection. Methods: This descriptive type of cross sectional study was conducted on 784 students randomly selected from eight medical colleges of Bangladesh, in the period of January 2019 to December 2019 with a pre tested self-administered questionnaire. Results: Study revealed that a total of 784 students responded, out of which 318(40.6%) males and 466(59.4%) females. Among them 726(92.6%) students wanted to do post-graduation after graduation. The leading reasons for selecting future career were personal preference 348(50.6%), self confidence 272(39.1%) and to take care of other family members 223(32.9%). Conclusion: Study recommended that orientation and career counseling at different stages in undergraduate medical education may help students and future doctors to choose their specialty for career as per the community healthcare needs. Bangladesh Journal of Medical Education Vol.14(1) January 2023: 63-69